1994
DOI: 10.1118/1.597337
|View full text |Cite
|
Sign up to set email alerts
|

A superconducting cyclotron for neutron radiation therapy

Abstract: The physical and clinical specifications of a neutron therapy facility utilizing a superconducting cyclotron are presented. The cyclotron and its support system are described. Details of the operation of the cyclotron in a hospital environment are given; the requirements of the helium liquifier and cryogenic system are described together with a summary of its mode of operation. The simplicity of the cyclotron control system is discussed. The physical characteristics of the neutron beam are described. The centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…This shield comprised two layers; the first layer (item E in figure 1) was up to 29 cm thick, and the second layer (item F in figure 1) was 6 cm thick, totaling up to 35 cm of shielding. For the final collimator (item A in figure 1), brass was replaced with tungsten alloy, a commonly used material for multi-leaf collimators (cf Maughan et al 1994, Bues et al 2005, Pönisch et al 2006, Jang et al 2006, Tacke et al 2006, Svensson et al 2007. The upstream collimator (item G in figure 1), also made of tungsten alloy, was located immediately downstream of the range-shifting plates (162 cm away from the surface of the patient and 186 cm upstream of isocenter).…”
Section: Modeling Of the Nozzle Modificationsmentioning
confidence: 99%
“…This shield comprised two layers; the first layer (item E in figure 1) was up to 29 cm thick, and the second layer (item F in figure 1) was 6 cm thick, totaling up to 35 cm of shielding. For the final collimator (item A in figure 1), brass was replaced with tungsten alloy, a commonly used material for multi-leaf collimators (cf Maughan et al 1994, Bues et al 2005, Pönisch et al 2006, Jang et al 2006, Tacke et al 2006, Svensson et al 2007. The upstream collimator (item G in figure 1), also made of tungsten alloy, was located immediately downstream of the range-shifting plates (162 cm away from the surface of the patient and 186 cm upstream of isocenter).…”
Section: Modeling Of the Nozzle Modificationsmentioning
confidence: 99%
“…As the studies outlined above had demonstrated a clear advantage to neutron therapy in terms of local control and survival for prostate cancer, it was our primary objective to show that this treatment could be delivered safely [8][9][10][11].…”
Section: Discussionmentioning
confidence: 98%
“…Neutron irradiation was conducted at the Gershenson Radiation Oncology Center (Harper Hospital, Detroit, MI) superconducting cyclotron, 30 at a dose rate of 55 cGy/min. The fast neutron facility produces a beam by accelerating 48.5 MeV deuterons onto a beryllium target.…”
Section: Irradiation Procedures and Drug Exposurementioning
confidence: 99%